Assessing the Veterans Affairs Surgical Quality Improvement Program Risk Calculator in Cholecystectomy. Issue 6 (June 2018) - Imran, Jonathan B.; Renteria, Oswaldo; Ruiz, Maria; Pham, Thai H.; Mokdad, Ali A.; Huerta, Sergio
The Veterans Affairs Surgical Quality Improvement Program (VASQIP) risk calculator has been validated for several operations but has not been assessed specifically for cholecystectomy. Our aim was to externally validate the VASQIP calculator's accuracy in predicting 30-day morbidity and mortality (M&M) for patients undergoing cholecystectomy. A retrospective review of patients undergoing cholecystectomy at the North Texas Veterans Affairs hospital was performed. The VASQIP risk calculator was used to determine predicted 30-day M&M, which was compared with actual M&M. The predictive accuracy of the Veterans Affairs risk calculator was assessed using the C-statistic and a graphical assessment of a locally weighted least squares regression smoother. Overall, 848 patients were included in the study. Actual M&M were 6.3 and 0.94 per cent, respectively, whereas predicted M&M were 6.0 and 0.54 per cent. The C-statistic was 0.75 for morbidity and 0.78 for mortality. In our analysis, the VASQIP risk calculator reasonably predicted 30-day M&M.